'Have You a Happy Voice?': Women's Voices and the Talkie Revolution in Britain 1929–1932. Issue 2 (December 2018) - Porter, Laraine
Abstract : The arrival of sound cinema in Britain created a vogue for particular kinds of voices and the quest for the elusive 'talkie' voice. The new recording technology favoured deeper, more resonant male voices while women's voices in the higher register did not record so well. This problem particularly affected British female stars not previously stage-trained in voice projection or those like Mabel Poulton with pronounced accents or voices that did not match their silent screen images. Many young women stars had been cast for their looks and glamour while older female character actors who had graduated in the theatre fared much better during the transition to sound. This article examines the opprobrium directed at the female voice in the 1920s, from early BBC broadcasting to the perceived dissonance between the visual images of female stars in silent cinema and how they sounded in the talkies.